2015
DOI: 10.1186/s12893-015-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotic colorectal surgery for laparoscopic surgeons with limited experience: preliminary experiences for 40 consecutive cases at a single medical center

Abstract: BackgroundWe present our preliminary experiences and results for forty consecutive patients with colorectal cancer (CRC) who were treated by robotic surgery.MethodsBetween May 2013 and September 2014, forty patients with CRC received robotic surgery at a single institution. The clinicopathological features and perioperative parameters were retrospectively analyzed.ResultsOf the 40 patients with CRC, 33 (82.5 %) had rectal cancers, and 22 (66.7 %) of those 33 patients also underwent pre-operative concurrent che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
6
25
0
1
Order By: Relevance
“…shown that complete TME with adequate circumferential margin (CRM) significantly affects the OS and local recurrence [2,3]. The first laparoscopic colectomy was performed in 1991 [16], which was then performed increasingly by surgeons as an alternative intervention for achieving better shortterm outcome compared with open surgery. Nevertheless, laparoscopic rectal TME is challenging owing to the limited anatomic pelvic surgical plane, rigidity of scope, hand tremor of camera-holding assistant, and resolution of two-dimensional visualization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shown that complete TME with adequate circumferential margin (CRM) significantly affects the OS and local recurrence [2,3]. The first laparoscopic colectomy was performed in 1991 [16], which was then performed increasingly by surgeons as an alternative intervention for achieving better shortterm outcome compared with open surgery. Nevertheless, laparoscopic rectal TME is challenging owing to the limited anatomic pelvic surgical plane, rigidity of scope, hand tremor of camera-holding assistant, and resolution of two-dimensional visualization.…”
Section: Discussionmentioning
confidence: 99%
“…This shortcoming paved way for the first robotic colon surgery in 2002, and this new minimally-invasive system tried to overcome the disadvantages of the conventional LS and improve the clinical outcomes. Additionally, the learning curve for RS is reported to be lesser than conventional LS [16,17]. In current modern medicine, robotic surgery is considered as a revolutionary procedure and one of the best treatment options for patients with RC.…”
Section: Discussionmentioning
confidence: 99%
“…The first laparoscopic colectomy was performed in 1991 [16], which was then performed increasingly 8 by surgeons as an alternative intervention for achieving better short-term outcome compared with open surgery. Nevertheless, laparoscopic rectal TME is challenging owing to the limited anatomic pelvic surgical plane, rigidity of scope, hand tremor of camera-holding assistant, and resolution of two-dimensional visualization.…”
Section: Discussionmentioning
confidence: 99%
“…В целом при оценке периоперационных параметров в нашем исследовании обе группы малоинвазивных операций оказались со-поставимы по средней величине кровопотери, частоте конверсий, при этом РА операции отличались боль-шей средней продолжительностью. Полученные нами результаты сходны с данными литературы [15][16][17][18]. В некоторых исследованиях отмечается меньшая кро-вопотеря при РА операциях по сравнению с ЛС, что относится к одному из преимуществ РА техноло-гии, однако в нашей работе это различие не было статистически значимым.…”
Section: Discussionunclassified